Preparation method, product and application of antistatic pre-dispersion for PVC (polyvinyl chloride) film
By using an antistatic agent bound to a carboxylated Mxene in PVC membrane structural materials, combined with a hyperbranched flow improver, the problem of insufficient durability of existing antistatic agents is solved, and the durable antistatic effect and stable performance of PVC membrane structural materials are achieved.
Patent Information
- Application Number
- CN202411711788.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The existing antistatic agents are insufficient in PVC film structural materials and are susceptible to ambient temperature/humidity, resulting in a decrease in the antistatic effect or failure.
The antistatic predispersion for PVC film was prepared by combining the aminolated ionic liquid-CNT complex with carboxylated Mxene to improve dispersion and processing flow through a hyperbranched flow improver.
The uniform dispersion of PVC film structural materials and the durability and stability of the antistatic effect are achieved, the dependence on ambient temperature/humidity is reduced, and the wear resistance and service life of the material are improved.
Smart Images

Figure BDA0005155932460000031 
Figure BDA0005155932460000051 
Figure BDA0005155932460000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of antistatic PVC materials, and in particular to a preparation method, product and application of an antistatic predispersion for PVC film. Background Art
[0002] Polyvinyl chloride (PVC) membrane structural materials have the characteristics of excellent performance, easy shaping, and low price. They are widely used in light box advertising materials, mine air duct materials, and building materials. In some special occasions such as coal mines, oil fields, and chemicals, there are strict requirements for the antistatic and flame retardant properties of materials. The static sparks and static accumulation generated during use are potential safety hazards and risks. However, high-molecular materials for mines, such as mine air duct materials and safety conveyor belts, have almost no antistatic function. If PVC membrane structural materials are given antistatic properties, their application in textiles, chemicals, coal mines, semiconductors, and electronics will be expanded.
[0003] The common method for antistatic PVC membrane structural materials is to add antistatic agents or conductive fillers. At present, the antistatic agents used in PVC membrane structural materials are mainly cationic surfactants such as quaternary ammonium salts, polymer surfactants, and conductive carbon black. However, surfactant-type antistatic agents are easy to migrate and precipitate, and their durability is insufficient; in addition, they are highly dependent on environmental humidity, and the antistatic effect will be reduced or even ineffective under low humidity conditions. After washing and wiping, the antistatic performance of polymer antistatic products decreases and the aging performance is poor. The amount of conductive carbon black required to meet the antistatic requirements is high, and the flexibility of the product becomes poor, which limits its wider application field. Among other antistatic agents, ionic liquids have good antistatic properties but high viscosity and poor dispersibility in PVC materials. Carbon nanotubes (CNT) also have good antistatic properties, but they are easy to agglomerate in the PVC matrix.
[0004] The existing antistatic agents have poor wear resistance, easy migration and are affected by the ambient temperature / humidity, which leads to insufficient antistatic durability of PVC film structure materials. Therefore, the selection and modification of antistatic agents for PVC has become one of the latest research hotspots in this field. CN114316473A carboxylates carbon nanotubes and then chlorinates them, thereby grafting them with hydroxyethyl imidazolium tetrafluoroborate ion liquid to obtain a new antistatic agent and apply it to PVC to prepare antistatic sealing strips. However, the surface resistance of the product is as high as 10 10 CN105670162A uses gum arabic to modify carbon nanotubes to improve the dispersibility of carbon nanotubes, and then combines with ionic liquid by anionic ultrasound to prepare PVC soles. The surface resistance of the product is 10 5 ~10 7CN118791809A uses silane-modified carbon black and imidazole bromide ion liquid grafting as antistatic materials for PVC plastics and introduces TENPO (2,2,6,6-tetramethylpiperidinium nitrogen-oxide-compound) to improve the compatibility of antistatic agents with PVC. The surface resistance of the resulting PVC material is reduced to 10 5 Ω, but its strength is lower.
[0005] However, for PVC film structures, such as PVC film or PVC film coated on the surface of a substrate, the antistatic durability of the antistatic PVC film structure material still needs to be improved. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention aims to provide a preparation method, product and application of an antistatic pre-dispersion for PVC film. The technical solution of the present invention is as follows.
[0007] First, the present invention provides a method for preparing an antistatic predispersion for PVC film, wherein the antistatic predispersion for PVC film contains an antistatic agent, a first plasticizer, an auxiliary dispersant and a hyperbranched flow improver, wherein the weight ratio of the antistatic agent, the first plasticizer, the auxiliary dispersant and the hyperbranched flow improver is (1-5): (30-50): (0.2-1): (2-4); wherein the method for preparing the antistatic agent comprises the following steps:
[0008] A1: CNTs are dispersed in deionized water, and an amino ionic liquid is added, dispersed, and dried at 100° C. to 120° C. to obtain an amino ionic liquid-CNT composite, wherein the weight ratio of the amino ionic liquid to CNT is (1-2):1.
[0009] A2: Take Mxene and perform carboxylation modification with a carboxylation solution to obtain carboxylated Mxene, disperse the aminated ionic liquid-CNT composite and the carboxylated Mxene in deionized water, and dry at 90° C. to 110° C. to obtain an antistatic agent; the weight ratio of the aminated ionic liquid-CNT composite to the carboxylated Mxene is 1:(0.5 to 2).
[0010] Preferably, in step A1, the aminated ionic liquid is selected from one or more of 1-aminopropyl-3-methylimidazolium nitrate, 1-aminoethyl-3-methylimidazolium bromide, 1-aminopropyl-3-methylimidazolium tetrafluoroborate, and 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0011] Preferably, in step A1, the CNT has a length of 0.5 μm to 10 μm and a diameter of 5 nm to 30 nm.
[0012] Preferably, in step A2, the Mxene is selected from one or more of Ti2CTx, Ti3C2Tx, Nb2CTx, Nb4Ti2NTx, and Ti4N3Tx, Tx is a surface functional group, and Tx is selected from one or more of -OH, -F, and -Cl;
[0013] Preferably, in step A2, the carboxylation solution is selected from one or more of sulfuric acid, acetic acid, chloroacetic acid and citric acid.
[0014] Preferably, the first plasticizer is selected from one or more of dimethyl phthalate (DMP), diethyl phthalate (DEP), dibutyl phthalate (DBP), dioctyl phthalate (DOP), and diisononyl phthalate (DINP). Further preferably, the first plasticizer is DINP.
[0015] Preferably, the auxiliary dispersant is selected from one or more of fatty acid polyoxyethyl ether ester, pentaerythritol stearate, and glyceryl monostearate. Further preferably, the auxiliary dispersant is fatty acid polyoxyethyl ether ester.
[0016] Preferably, the hyperbranched flow improver is selected from one or more of hyperbranched polyesters, hyperbranched polyimides, and hyperbranched epoxy resins. Further preferably, the hyperbranched flow improver is selected from hyperbranched polyester flow improvers.
[0017] Preferably, the method for preparing the antistatic predispersion for PVC film further comprises the following steps:
[0018] A3: Mix the antistatic agent, the first plasticizer and the auxiliary dispersant, grind and disperse them to obtain a dispersed slurry;
[0019] A4: Add hyperbranched flow improver to the dispersed slurry and mix well to obtain an antistatic predispersion for PVC film.
[0020] Second, the present invention provides a PVC film structure material containing the aforementioned antistatic pre-dispersion for PVC film, comprising a base fabric and the following materials:
[0021]
[0022] The preparation method of the PVC film structure material comprises the following steps: mixing PVC resin, a second plasticizer, a heat stabilizer and heavy calcium carbonate, adding the antistatic pre-dispersion for PVC film, mixing, uniformly coating on the surface of the base fabric, and plasticizing at 190° C. to 210° C. for 1 min to 3 min to obtain the PVC film structure material.
[0023] Preferably, the PVC resin is PVC paste resin.
[0024] Preferably, the second plasticizer is selected from one or more of DMP, DEP, DBP, DOP and DINP.
[0025] Preferably, the heat stabilizer is selected from one or more of a barium / zinc composite stabilizer, a composite rare earth stabilizer, and hydrotalcite.
[0026] Preferably, the mesh size of the heavy calcium carbonate is 400-800 mesh.
[0027] Preferably, the base fabric is PET fiber fabric.
[0028] Preferably, the coating weight of the PVC film structure material is 100 g / m 2 ~180g / m 2 .
[0029] Thirdly, the use of the antistatic predispersion for PVC film or PVC film structure material provided by the present invention in the preparation of antistatic PVC material, the antistatic PVC material is suitable for light box advertising material, mine wind tube material and building material, etc. It is also suitable for special occasions such as coal mines, oil fields, chemical plants, etc.
[0030] The present invention has the following beneficial effects:
[0031] 1. The antistatic pre-dispersion for PVC film prepared by the present invention is evenly dispersed in the PVC matrix and is not easy to agglomerate. The hyperbranched flow improver used can reduce the flocculation of the amino ionic liquid-CNT / Mxene, further improve the dispersibility and improve the processing fluidity.
[0032] 2. The PVC film structure material prepared by the antistatic predispersion for PVC film of the present invention has a smooth surface, good uniformity, low dependence on ambient temperature / humidity, and a long-lasting antistatic effect. At the same time, the PVC film structure material prepared by the present invention has good wear resistance, is not easy to migrate, has stable performance, and has a long service life.
[0033] 3. The antistatic predispersion for PVC film prepared by the present invention can reduce the viscosity of PVC slurry, has good fluidity, and can appropriately reduce the amount of plasticizer added in the PVC system. DETAILED DESCRIPTION
[0034] The antistatic pre-dispersion for PVC film, PVC film structure product and effect provided by the present invention are described in detail below in conjunction with specific embodiments. The embodiments are only used to further illustrate the present invention and are not to be regarded as limiting the scope of protection of the present invention. The materials, instruments and equipment used in the following embodiments are all commonly used and commercially available materials, instruments and equipment. The CNT raw materials have a length range of 0.5 μm to 5 μm and a diameter range of 5 nm to 30 nm, which are purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. Mxene was purchased from Beijing Beike New Material Technology Co., Ltd.
[0035] The antistatic predispersion for PVC film and the PVC film structure material of the present invention are prepared by the following method:
[0036] 1. Take CNT and add it to deionized water, and disperse it evenly by ultrasonic; add aminated ionic liquid and disperse it evenly by ultrasonic, and heat the obtained suspension at 100℃~120℃ to obtain aminated ionic liquid-CNT composite.
[0037] 2. Take Mxene and use carboxylation solution to perform carboxylation modification, separate, and obtain carboxylated Mxene. Take the amino ionic liquid-CNT composite and carboxylated Mxene and disperse them in deionized water, disperse them evenly by ultrasonication, and dry them at 90°C to 110°C to obtain an antistatic agent.
[0038] 3. Mix the antistatic agent, the first plasticizer and the auxiliary dispersant, grind and disperse them to obtain a dispersed slurry; add a hyperbranched flow improver, and ultrasonically disperse them to obtain an antistatic pre-dispersion for PVC film.
[0039] 4. Take PVC resin, the second plasticizer, the heat stabilizer, and heavy calcium carbonate, stir and mix well, add the antistatic pre-dispersion for PVC film obtained in step 3, mix well, and evenly apply it on the front and back of the base fabric, plasticize, and obtain the PVC film structure material.
[0040] The carboxylation modification of Mxene belongs to the conventional technology in this field, which can be found in the literature:
[0041] (1) Xie Lan. Preparation of chloroacetic acid modified two-dimensional MXene material (Ti3C2Tx) and its adsorption of radioactive nuclides uranium and thorium[D]. University of South China, 2022.
[0042] (2) Yang Jie. Study on thermal stability of functionalized MXenes-enhanced silicone rubber[D]. Beijing University of Chemical Technology, 2022.
[0043] (3) Yan Jia. Study on the performance of citric acid modified alkaline Ti3C2MXene absorbing Eu(Ⅲ) and basic red 46[D]. University of South China, 2022.
[0044] Example 1 Preparation of antistatic predispersion for PVC film and PVC film structural material
[0045] In this embodiment, three kinds of antistatic pre-dispersions for PVC films and PVC film structure material experimental products are prepared, and the ingredient list and parameters of different experimental products are shown in Table 1. The parts in Table 1 represent weight parts and their ratios.
[0046] Table 1 Ingredients and parameters of antistatic pre-dispersion for PVC film and PVC film structural materials
[0047]
[0048] The preparation method of the antistatic pre-dispersion for PVC film and the PVC film structure material is as follows, taking Experiment 1 as an example:
[0049] 1. Take 1 part of CNT and add it to an appropriate amount of deionized water, and disperse it evenly by ultrasonication; add 1 part of 1-aminoethyl-3-methylimidazolium bromide (i.e., aminated ionic liquid), and disperse it evenly by ultrasonication. The suspension is placed in a vacuum oven and dried at 110°C to obtain an aminated ionic liquid-CNT composite.
[0050] 2. Carboxylate Mxene (Ti3C2Tx) with chloroacetic acid solution, separate and obtain carboxylated Mxene. Disperse 1 part of amino ionic liquid-CNT composite and 1 part of carboxylated Mxene in deionized water, disperse evenly by ultrasonication, and dry at 105°C to obtain an antistatic agent;
[0051] 3. Mix 1 part of antistatic agent, 40 parts of DINP and 1 part of fatty acid polyoxyethyl ether ester evenly, place in a three-roll mill, grind and disperse at 500 rpm for 90 minutes to obtain a dispersed slurry; add 2 parts of hyperbranched polyester flow improver, disperse evenly by ultrasonication, and obtain an antistatic pre-dispersion for PVC film.
[0052] 4. Take 100 parts of PVC paste resin, 60 parts of DINP plasticizer, 2.5 parts of barium / zinc composite stabilizer, 30 parts of 800 mesh heavy calcium carbonate, stir and mix, add 15 parts of PVC film antistatic pre-dispersion, mix and evenly apply on the front and back of PET fiber fabric, the coating weight is 160g / m 2 , plasticized at 200℃ for 2min to obtain PVC membrane structure material.
[0053] For experimental samples 2 and 3, the drying conditions in step 2 were drying at 90° C. and drying at 110° C. For experimental samples 2 and 3, the plasticizing conditions in step 4 were plasticizing at 210° C. for 1 min and plasticizing at 190° C. for 3 min.
[0054] Example 2 Performance test of PVC membrane structure material
[0055] Referring to the materials and preparation method of Example 1, different comparative products were prepared respectively:
[0056] Comparative product 1: The difference from experimental product 1 is that no antistatic pre-dispersion for PVC film is added in step 4 (ie, steps 1-3 do not exist), and the remaining steps and conditions are the same to prepare a PVC film structure material.
[0057] Comparative product 2: The difference from experimental product 1 is that 0.5 parts of 1-aminoethyl-3-methylimidazolium bromide is added in step 1, and the remaining steps and conditions are the same to prepare a PVC membrane structure material.
[0058] Comparative product 3: The difference from experimental product 1 is that in step 2, 3 portions of the amino ionic liquid-CNT composite are taken, and the remaining steps and conditions are the same to prepare a PVC membrane structure material.
[0059] Comparative product 4: The difference from experimental product 1 is that 3 portions of carboxylated Mxene are taken in step 2, and the remaining steps and conditions are the same to prepare a PVC membrane structure material.
[0060] Comparative product 5: The difference from experimental product 1 is that no hyperbranched polyester flow improver is added in step 3, and the remaining steps and conditions are the same to prepare a PVC membrane structure material.
[0061] Performance Testing:
[0062] The tensile strength of polyvinyl chloride membrane structural materials was tested according to the method specified in GB / T 3923.1-2013.
[0063] The peel strength of polyvinyl chloride membrane structural materials was tested according to the method specified in FZ / T 60039-2013.
[0064] The surface resistivity of polyvinyl chloride membrane structural materials was tested according to the method specified in GB / T 1410-2006.
[0065] The wear resistance of polyvinyl chloride membrane structural materials is tested according to the method specified in GB / T 10006-2021.
[0066] The durability of polyvinyl chloride membrane structure materials was tested according to the method specified in GB / T 23989-2009.
[0067] Table 2 Performance test results of PVC structural materials prepared from experimental products 1 to 3 and comparative products 1 to 5:
[0068]
[0069] From the performance test results in Table 2, it can be seen that the tensile strength, peel strength and antistatic properties of the PVC film structure materials obtained by the experimental products 1 to 3 prepared by the preparation method of the present invention are better than those of the comparative products 1 to 5. The added conductive filler not only limits the movement and orientation of the PVC molecular chain, improves the mechanical properties of the PVC film structure material, but also greatly improves its antistatic performance. The aspect ratio of CNT is large, the agglomeration effect is significant, and it is easy to form agglomerates, resulting in poor antistatic effect, while the agglomeration and entanglement of CNT modified by ionic liquid are significantly weakened; Mxene intercalates CNT, and its dispersibility and antistatic properties are further improved. Due to the presence of hyperbranched flow improver, the processing fluidity of the antistatic pre-dispersion is improved, and a continuous conductive network structure can be formed in the PVC matrix, with excellent antistatic effect. After washing and wear resistance test, the surface resistance of the PVC film structure material has no obvious change, indicating that its antistatic effect is long-lasting and stable. In addition, the PVC film structure material obtained by the embodiment of the present invention has little dependence on environmental temperature / humidity, is not easy to migrate, and has a long service life. The method is simple and efficient, low cost, and easy to achieve industrial mass production.
[0070] The above are several preferred embodiments of the present invention, which are described in detail, but the protection of the present invention is not limited thereto. It should be noted that any modification and improvement made by a person skilled in the art to the technical solution of the present invention without departing from the overall concept of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing an antistatic predispersion for PVC film, characterized in that: The antistatic pre-dispersion for PVC film contains an antistatic agent, a first plasticizer, an auxiliary dispersant and a hyperbranched flow improver, wherein the weight ratio of the antistatic agent, the first plasticizer, the auxiliary dispersant and the hyperbranched flow improver is (1-5): (30-50): (0.2-1): (2-4); the preparation method of the antistatic agent comprises the following steps: A1: Disperse CNT in deionized water, add aminated ionic liquid, disperse, and dry at 100° C. to 120° C. to obtain an aminated ionic liquid-CNT composite; the weight ratio of the aminated ionic liquid to CNT is (1-2):1; A2: Take Mxene and perform carboxylation modification with a carboxylation solution to obtain carboxylated Mxene, disperse the aminated ionic liquid-CNT composite and the carboxylated Mxene in deionized water, and dry at 90° C. to 110° C. to obtain an antistatic agent; the weight ratio of the aminated ionic liquid-CNT composite to the carboxylated Mxene is 1:(0.5 to 2).
2. The method for preparing an antistatic predispersion for PVC film according to claim 1, characterized in that: In step A1, the aminated ionic liquid is selected from one or more of 1-aminopropyl-3-methylimidazolium nitrate, 1-aminoethyl-3-methylimidazolium bromide, 1-aminopropyl-3-methylimidazolium tetrafluoroborate, and 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
3. The method for preparing an antistatic predispersion for PVC film according to claim 1, characterized in that: In step A2, the Mxene is selected from one or more of Ti2CTx, Ti3C2Tx, Nb2CTx, Nb4Ti2NTx, and Ti4N3Tx, Tx is a surface functional group, and Tx is selected from one or more of -OH, -F, and -Cl.
4. The method for preparing an antistatic predispersion for PVC film according to claim 1, characterized in that: In step A2, the carboxylation solution is selected from one or more of sulfuric acid, acetic acid, chloroacetic acid, and citric acid.
5. The method for preparing an antistatic predispersion for PVC film according to claim 1, characterized in that: In step A1, the CNT has a length of 0.5 μm to 10 μm and a diameter of 5 nm to 30 nm.
6. The method for preparing an antistatic predispersion for PVC film according to claim 1, characterized in that: The first plasticizer is selected from one or more of dimethyl phthalate (DMP), diethyl phthalate (DEP), dibutyl phthalate (DBP), dioctyl phthalate (DOP), and diisononyl phthalate (DINP).
7. The method for preparing an antistatic predispersion for PVC film according to claim 1, characterized in that: The auxiliary dispersant is selected from one or more of fatty acid polyoxyethyl ether ester, pentaerythritol stearate, and glyceryl monostearate.
8. The method for preparing an antistatic predispersion for PVC film according to claim 1, characterized in that: The hyperbranched flow improver is selected from one or more of hyperbranched polyesters, hyperbranched polyimides, and hyperbranched epoxy resins.
9. The method for preparing an antistatic predispersion for PVC film according to claim 8, characterized in that: The hyperbranched flow improver is selected from hyperbranched polyester flow improvers.
10. The method for preparing an antistatic predispersion for PVC film according to claim 1, characterized in that: The method for preparing the antistatic pre-dispersion for PVC film further comprises the following steps: A3: Mix the antistatic agent, the first plasticizer and the auxiliary dispersant, grind and disperse them to obtain a dispersed slurry; A4: Add hyperbranched flow improver to the dispersed slurry and mix well to obtain an antistatic predispersion for PVC film.
11. A PVC film structural material prepared from an antistatic predispersion for PVC film prepared by the method for preparing an antistatic predispersion for PVC film according to any one of claims 1 to 10, characterized in that: The PVC membrane structure material comprises a base fabric and the following materials: 100 parts by weight of PVC resin; 10-25 parts by weight of antistatic pre-dispersion for PVC film; 40 to 60 parts by weight of a second plasticizer; 2 to 3 parts by weight of heat stabilizer; Heavy calcium carbonate 20-30 parts by weight; The preparation method of the PVC film structure material comprises the following steps: mixing PVC resin, a second plasticizer, a heat stabilizer and heavy calcium carbonate, adding the antistatic pre-dispersion for PVC film, mixing, uniformly coating on the surface of the base fabric, and plasticizing at 190° C. to 210° C. for 1 min to 3 min to obtain the PVC film structure material.
12. The PVC membrane structural material according to claim 11, characterized in that: The PVC resin is PVC paste resin.
13. The PVC membrane structure material according to claim 11, characterized in that: The second plasticizer is selected from one or more of DMP, DEP, DBP, DOP and DINP.
14. The PVC membrane structural material according to claim 11, characterized in that: The heat stabilizer is selected from one or more of a barium / zinc composite stabilizer, a composite rare earth stabilizer, and hydrotalcite.
15. The PVC membrane structural material according to claim 11, characterized in that: The mesh number of the heavy calcium carbonate is 400 mesh to 800 mesh.
16. The PVC membrane structural material according to claim 11, characterized in that: The base fabric is PET fiber fabric.
17. The PVC membrane structural material according to claim 11, characterized in that: The coating weight of the PVC membrane structure material is 100g / m 2 ~180g / m 2 .
18. Use of the antistatic predispersion for PVC film obtained by the method for preparing an antistatic predispersion for PVC film according to claim 1 or the PVC film structure material according to claim 11 in preparing antistatic PVC material.
Citation Information
Patent Citations
Preparation method of high-toughness antistatic PVC (polyvinyl chloride) composite sole material
CN105670162A
Antistatic sealing strip and preparation method thereof
CN114316473A
Antistatic PVC plastic and preparation method thereof
CN118791809A
Aminooimidazole ionic liquid modified graphene nanosheet / polyethylene composite material and preparation method thereof
CN106098400A
Antistatic organosilicon pressure-sensitive adhesive containing electron transport material and preparation of adhesive
CN112608689A
Cited By
Environment-friendly wear-resistant long-acting antistatic PVC aggregate and preparation method thereof
CN120842754A
Environment-friendly long-wearing antistatic PVC granules and preparation method thereof
CN120842754B